The Impact of Website Quality on Brand Loyalty: The Mediating Role of Customer Engagement Behavior - Ginanjar, Dudung; Astuti, Widhy Tri; Arif, Nina Fapari (Strata International Journal of Social Issues, 2025)
In the digital transformation era, website quality has become a key strategic element in enhancing customer experiences and fostering brand loyalty, particularly within the hospitality sector. This study investigates the impact of website quality on brand loyalty, with customer engagement behavior acting as a mediating variable. Drawing on empirical data from guests of Merapi Merbabu Hotel Yogyakarta, the research employs a quantitative, hypothesis-driven approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze relationships among key constructs: website quality, customer engagement behavior, and brand loyalty. The findings reveal that website quality has a significant direct effect on brand loyalty, and also positively influences customer engagement behavior, which in turn mediates the relationship between website quality and brand loyalty. This highlights the pivotal role of digital customer engagement in translating website excellence into long-term brand loyalty. The study provides both theoretical and practical implications, emphasizing the necessity for hotel management to continuously improve digital interface quality and foster interactive online experiences. These strategies are vital for strengthening emotional connections with customers and ensuring sustainable competitive advantage in the hospitality industry.